Sus Oef as the Theology of Indonesian Ethnic Marriage Dowry - Halim Wiryadinata; Fonny Natalia Joseph (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2023)
This research aims to show that the ethnic theology of wedding dowry builds the relationship between two prominent families as the foundation of society. The main issue from the previous research is economic instability for a household in marriage life. The original value of the wedding dowry in the Bone village, NTT, is to exhibit the reflection of the teaching from the forefathers to bond up the relative. The acknowledgment of the wedding dowry is the acceptance of the stranger into the big family as the expression of the building relative's value. Therefore, Sus Oef – called – is the way of expressing the idea of reflecting on the ritual of the people in the Bone village among the society. Through the sociological religion method, this research is conducted to reveal the perspective emic of the issue. The sociological analysis helps this research to see how the anatomy of Sus Oef works in the light of the Biblical narrative. The result of this study is that religion leads to extensive family bonding in the wedding ceremony. Finally, the conclusion presents how religion legitimates the family's bonding as the ethnic theological wedding dowry. The result of this study applies to church human resources education to understand the ethnic theology of wedding dowry as a part of cultural existence to recognize the extensive family bonding through the wedding dowry.